Reading achievement declines during the COVID-19 pandemic: evidence from 5 million U.S. students in grades 3–8 - Kuhfeld, Megan; Lewis, Karyn; Peltier, Tiffany (Reading & writing, 2023)
The COVID-19 pandemic has been an unprecedented disruption in students’ academic development. Using reading test scores from 5 million U.S. students in grades 3–8, we tracked changes in achievement across the first two years of the pandemic. Average fall 2021 reading test scores in grades 3–8 were .09 to .17 standard deviations lower relative to same-grade peers in fall 2019, with the largest impacts in grades 3–5. Students of color attending high-poverty elementary schools saw the largest test score declines in reading. Our results suggest that many upper elementary students are at-risk for reading difficulties and will need targeted supports to build and strengthen foundational reading skills.